The curse of poverty - Reed, Louise (My University, 1891)
Introduction: We often hear some long faced, “I am resigned to my fate,” person say solemnly. “What a blessing is poverty, and what a curse is wealth!” They are the people who speak with disdain of the “almighty dollar”, the “filthy rich”, which is the root of all evil; but they love the people of those same dollars as well as their neighbors, and many of them would hold on to a little, dirty, copper cent till the very Indian on it howled from pain. After all, is it not the want of the “almighty dollar” that is the root of all evil rather than the presence of it? Is it not the intense longing to possess rather than the possession which causes so much crime and misery? And, is it not more than all, the necessity of the many waring against the luxurious wants of the few? What is there that so maddens a man as the sight of a lady dressed in the richest silk and heaviest furs when his own poor wife has hardly enough clothing to cover her shivering limbs and every thread in her thin garment counts so much of the toil, and sacrifice she has made some where to obtain the little that she has?
Citation: Reed, Louise. The curse of poverty. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Sociology; Wealth; Poverty; Theses; Manuscripts (documents)